Unmet Aspirations as an Explanation for the Age U-shape in Wellbeing - Hannes Schwandt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
An emerging economic literature has found evidence that wellbeing follows a U-shape over age. Some theories have assumed that the U-shape is caused by unmet expectations that are felt painfully in midlife but beneficially abandoned and experienced with less regret during old age. In a unique panel of 132,609 life satisfaction expectations matched to subsequent realizations, I find that future life satisfaction is strongly overestimated when young and underestimated during old age. This pattern is stable over time and observed within cohorts as well as across socio-economic groups. These findings support theories that unmet expectations drive the age U-shape in wellbeing.
Keywords: I30; J10; D84; 330